The standard portfolio choice problem in Germany - Steffen Huck; Tobias Schmidt; Georg Weizsäcker (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2014)
We study an investment experiment conducted with a representative sample of German households. Respondents invest in a safe asset and a risky asset whose return is tied to the German stock market. Experimental investments correlate with beliefs about stock market returns and exhibit desirable external validity: they predict real-life stock market participation. But many households do not significantly react to an exogenous increase in the risky asset's return. The data analysis and analogous laboratory experiments suggest that task complexity decreases the responsiveness to incentives. Modifying the return of the (simpler) safe asset has a larger effect.
Keywords: D1; D14; D84; G11; 330; stock market expectations; stock market participation; portfolio choice; artefactual field experiment; financial literacy